Dampak Keluarga Broken Home Terhadap Relasi Orang Tua Dengan Anaknya dalam Web Series Bad Parenting - Selina Sebayang; Luh Putu Sendratari; Fitri Noviani (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Broken home describes a family that is in disarray because parents no longer care about the situation and circumstances of the family at home. The consequences of a broken home certainly greatly affect the relationship between parents and children in terms of communication, mental, psychological and education of the child. There have been many literary works that tell the relationship between children and parents that contain many meanings and moral messages. One of them is the bad parenting web series which provides an overview of the conditions in which parents are unable to provide good parenting to their children. This study aims to determine the impact of a broken home family on the relationship between parents and their children in the bad parenting web series as a source of learning sociology. The research method used is descriptive qualitative research to describe the impact of a broken home family on the relationship between parents and children in the Bad Parenting Web Series. The data analysis used is Roland Barthes' semiotic analysis. The research findings reveal that the storyline of the characterization by the main character shows Monica's character who is authoritarian, selfish and overprotective of her child. The existence of forms of bad parenting patterns carried out by the characters caused by various underlying factors that lead to a strained relationship between mother and father, coupled with children starting to grow up. There are aspects in the Bad Parenting web series that have the potential to be a source of learning Sociology. Sociology studies the relationship between parents and children as part of social interaction in the family. A good relationship between parents and children can help the development of children and create a harmonious family.